Gambaran Protein Urine pada Penderita Diabetes Melitus Tipe 2 di Puskesmas Cikajang - Nafsa Mutmaina, Gina; Sugiah; Puspita, Tantri; Lestari, Nabila Ajeng Wiji (LP4M STIKes Karsa Husada Garut, 2023)
Introduction: Type 2 diabetes mellitus is the most common type. In patients with type 2 diabetes mellitus the pancreas can still make insulin, but the quality of insulin is poor and cannot function properly so that blood glucose increases. The presence of protein in the urine is caused by leakage of plasma proteins from the glomerulus. Clinically detected proteinuria is abnormal and is usually an early marker of kidney disease. The purpose of this study was to determine the results of urine protein examination in patients with Type 2 Diabetes Mellitus at Cikajang Health Center. The purpose of this study was to determine the results of the description of urine protein levels in patients with type 2 diabetes mellitus at the Cikajang Health Center Method: the research used was descriptive research. The population in this study was 7,338 people. The sample size in this study was 30 respondents. The sampling technique used was purposive sampling technique. The variable in this study was urine protein levels in patients with type 2 DM examined using the dipstick method. Results: The results of this study obtained negative results (-) 19 people (64%), trace (±) 8 people (26%), positive 1 (+) 2 people (7%), positive 2 (++) 1 person (3%). The results of the study can be concluded that in this study there were more negative urine protein results compared to positive urine protein results. Conclusion. It can be concluded that in this study more results were negative urine protein compared to positive urine protein.